Pengaruh Penyaluran Kredit Usaha Rakyat, Non Performing Loan,Tingkat Suku Bunga Bank Indonesia dan CAR Terhadap Profitabilitas (Studi Kasus Pada PT Bank Rakyat Indonesia (PERSERO) TBK Periode 2010-2017) - Muhammad Andhika Wiranegara (JAF (Journal of Accounting and Finance), 2019)
The purpose of this study was to determine whether the level of People's Business Credit distribution, non-performing loans, Bank Indonesia interest rates and CAR can affect the level of profitability (Return On Asset) of PT Bank Rakyat Indonesia (Persero) Tbk, this study using secondary data sourced from the quarterly financial statements in the period 2010-2017. In managing the data that is owned, the author uses the SPSS version 20 data processing application. The data analysis technique used is multiple linear regression and to test the hypotheses of this study using t-statistical tests to test hypotheses partially and f-statistical tests to test hypothetically simultaneous. From the results of the tests that have been carried out in the Business Credit distribution, the interest rates of Bank Indonesia and CAR do not partially affect Return On Assets, while the non-performing loans affect Return On Assets. Simultaneously, the variable of People's Business Credit distribution, non-performing loans, Bank Indonesia interest rates and CAR has an effect on Return On Asset of 71.4 percent and the other is influenced by variables other than those studied. Key notes : Kredit Usaha Rakyat, Non Performing Loan, tingkat suku bunga Bank Indonesia, Capital Adequacy Ratio, Return On Asset.